On the system of two nonlinear difference equations xn+1=A+xn−1/yn, yn+1=A+yn−1/xn - G. Papaschinopoulos; C. J. Schinas (International Journal of Mathematics and Mathematical Sciences)
We study the oscillatory behavior, the periodicity and the asymptotic behavior of the positive solutions of the system of two nonlinear difference equations xn+1=A+xn−1/yn and yn+1=A+yn−1/xn, where A is a positive constant, and n=0,1,….